(untitled) (Marketing Jurnali, 2025)
This article is devoted to the marketing strategy and the mechanisms of its implementation in the higher education system of Uzbekistan, it analyzes the main types of marketing strategies used in the field of higher education and their main directions, the essence of the market of educational services and educational services is highlighted. specific features of services are based, marketing strategy in the higher education system and mechanisms of its implementation are researched, systematic work and main indicators implemented in the higher education system are analyzed, supply and demand for highly educated personnel is analyzed